Study the performance of porous pavement on urban thermal environment. Part 1: Field observation - Eusuf, Muhammad Abu; Jahn Kassim, Puteri Shireen; Ibrahim, Mansor (2008)

(untitled)
An observation and modelling study of thermal behaviour of porous pavement of an urban area, as related to the physical nature of the site, is presented. The measurement and calculations are made in comparison with a natural surface grass. The measurement program was conducted during the month of February 2008 at IIUM Gombak Campus.